EkoFundusz jako podmiot wspierający innowacyjność w ochronie środowiska w Polsce - Bartniczak, Bartosz (EcoFund as an Entity Supporting Innovation in Environment Protection in Poland, 2008)
Establishing EcoFund in Poland was one of the first in the world initiative of allocating a part of a government-secured debt for environmental protection purposes (ecoconversion of debts). The goal of the article is to show the history of EcoFund and to examine the role Ecofund plays in financing environmental protection in Poland. The article shows also the role which EchoFund plays in transfering a new technology in Poland in environment protection. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 45-52